Портретний живопис у романах М. Шолохова „Тихий Дон” і М. Стельмаха „Кров людська – не водиця” і „Хліб і сіль” - Адамович, Анастасія Євгенівна; Адамович, Анастасия Евгеньевна; Adamovych, Anastasiia (Акцент, 2009)
UK: У статті робиться спроба порівняльного аналізу портретного живопису романів М. Шолохова і М. Стельмаха. Об’єктом дослідження виступають такі твори, як „Тихий Дон” та „Кров людська – не водиця”, „Хліб і сіль”. Така постановка питання дозволить більш повно зрозуміти специфіку формування і розвитку характеру персонажів. EN: The article gives the comparative attempt of portraits of the novels written by M. Sholokhov and M. Stel’mah. The object of the research includes such works as „And Quiet Flows the Don” and „The Human’s Blood is Not Water”, „Bread and salt”. Such point of view will allow to more profound comprehension of the original conditions of the characters’ formation and of the evolution.
Portrait’s art in the novels „And Quiet flows the Don” by M. Sholokhov and „The human’s blood is not water” „Bread and salt” by M. Stel’mah
Keywords: порівняльний аналіз; М. Шолохов; М. Стельмах; M. Stel’mah; M. Sholokhov; formation and of the evolution; літературознавство